MAJOR DEPRESSIVE DISORDER IN ELDERLY PEOPLE AT ESF SANTA BÁRBARA, ARARIPINA-PE - e Silva Júnior, Roberth Pierson Moura; Moreira, Murilo Augusto; Araruna, Natália Ferraz; Piancó Neto, Luiz Leite; de Araújo, Luana Lucena; da Silva, Jued Cleiton; Barros, Eduarda Maria Dantas; Melo, Keyla Aparecida Alves de Sá Carneiro; Leal, Wolney Barros; Feijó, Daniel Bezerra Lenzzi; Bulhões, Paula Roberta Fernandes; Andriola, Igor Rodrigues (Seven Editora, 2025)
Geriatric depression is an emotional disorder that affects a growing number of elderly people around the world. This type of depression is not only manifested by classic symptoms of deep sadness, but it can also express itself in more subtle ways, such as excessive tiredness, irritability, and cognitive difficulties. In a global context, where the elderly population is growing rapidly, the recognition, early diagnosis, and appropriate treatment of geriatric depression become public health issues of great relevance. This work aims to provide guidance on depression and develop programs or activities that promote the mental health and well-being of the elderly, preventing and treating depression in the community. The place where the practice was carried out was at the ESF Santa Bárbara, in the municipality of Araripina-PE. The accomplishment of this work is justified because it is of great relevance to public health and the health of the elderly population in the community. Depression in the elderly is a growing and underdiagnosed public health problem. Often, the symptoms are confused with the normal consequences of aging, which makes it difficult to properly diagnose and treat. The Basic Health Units are the gateway to the health system of many elderly people, which makes them the ideal place for the identification and management of depression. Therefore, reducing this scenario is of paramount importance to reverse the increase in mental illnesses and act to promote and ensure the health of the elderly population.DOI: https://doi.org/10.56238/sevened2025.021-086